Fat Lives : a Feminist Psychological Exploration - Tischner, Irmgard (Women and psychology., 2013)
Ever caught somebody - or yourself - checking out the content of a 'fat' person's supermarket trolley? Ever wondered what lies behind this behaviour, or what it might be like to be at the receiving end of this judging gaze? Within the context of the current 'obesity debate', this book investigates the embodied experience of 'being large' from a critical psychological perspective. Using poststructuralist and feminist theories, the author explores the discourses available to and used by self-designated 'fat' individuals, as well as the societal power relationships that are produ.